PENGARUH FOTOGRAFI JURNALISTIK TERHADAP MASYARAKAT PADA MEDIA ONLINE - Rahmah Tasya Ad'nisa; Maya Purnama Sari (Fakultas Dakwah dan Komunikasi, 2021)
Through online media, people can find information wherever they are and whenever they need it. Photojournalism can record something quickly, and objectively, and contain news and information. The purpose of this study is to determine the effect of journalistic photography on society on online media so that there is an evaluation for journalistic photographers. This research method uses quantitative methods. Online media users need journalistic photography that is accurate, specific, concise, and complete in accordance with what is required by the community. Then photojournalism must fulfill the character of photojournalism so that the value of a photo will reflect itself, according to the characteristics and types of photojournalism itself.